Pengaruh Laju Aliran Air Sistem Evaporative Cooling Terhadap Temperatur Sistem Mesin Pengkondisian Udara - Mainil, Rahmat Iman; Jenvrizen, David; Aziz, Azridjal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Evaporative Cooling is an air conditioning system that uses water to cool and add moisture or humidity in the air flow, so ball temperature is dry become cooler before experiencesublimate process. Media temperature change influence coolant to water debit change whichis if water temperature the greater, therefore resulting water debit will get little conversely if water temperature gets little, therefore resulting water debit will be even greater. Media temperature change influence water cooler to its air humidity if coolant media temperature the greater therefore resulting air humidity also the greater too. On this research streaming debit that result effectiveness at the best which is in a row 1,2, 1,04, and 0,8 liters / minutes. Besides with marks sense purpose increase evaporative cooling can make kompresor'scharges gets demulcent.Keywords : Evaporative Cooling, Condenser, Relative Humidity, Power Compression.